Research And Development (R&D) Penelitian Yang Inovatif Dalam Pendidikan - Okpatrioka Okpatrioka (Institut Nalanda, 2023)
The focus of this paper is research and development, as an innovative, productive and meaningful form of educational research. This research aims to describe R&D research in the field of education. The focus of this research is the concept of R&D research in the field of education which is broken down into five sub-focuses, namely (1) The objectives of R&D research in the field of education, (1) The objectives of R&D research in the field of education, (2) The characteristics of R&D research in the field of education, (3) ) Characteristics of R&D research in the field of education, (4) Steps of R&D research in the field of education, and (5) advantages and disadvantages of R&D research in the field of education. This research uses a qualitative method of literature study. The conclusion of this research is that R&D research is more complicated and takes a long time to implement. Therefore, students who conduct R&D research must be patient and consistent in following each step of R&D research sequentially in order to produce a valid product.